Detection of Mycoplasma bovis in cattle with mastitis and respiratory problems in eastern Turkey - Karahan, M.; Kalin, R.; Atil, E.; Cetinkaya, B. (Bmj Publishing Group, 2010)
[Abstract Not Available]
Keywords: Infection; Diagnosis; Calves; Pcr